Tumor-Derived Exosomes Regulate Apoptosis of CD45+EpCAM+ Cells in Lung Cancer - Lu, Shixiang; Sun, Zhen; Liu, Lili; Li, Peng; Li, Bin; Li, Wenjing; Wu, Zhaojun; Zhao, Mingming; Liu, Wenna; Wang, Yongjie; Wang, Bin (Frontiers in Immunology, 2022)
Lung cancer has the highest mortality rate among human cancers, and the majority of deaths result from metastatic spread. The tumor microenvironment plays an important role in suppressing the immune surveillance and elimination of tumor cells. A few studies have reported the presence of CD45+EpCAM+ double-positive cells in cancer, but the underlying mechanism remains unclear with respect to how these cells originate and their function in cancer biology. In this study, we analyzed 25 lung tumor samples. We confirmed the presence of CD45+EpCAM+ cells in lung cancer, and these cells exhibited higher apoptosis than CD45+EpCAM− cells. Using co-culture of lung cancer cell-derived exosomes with healthy donor peripheral blood mononuclear cells, we recapitulated CD45+EpCAM+ cell formation and increased apoptosis that occurs in patients with primary lung cancer. Further analysis suggested that microRNAs in lung cancer cell-derived exosomes may alter the gene expression profile of CD45+EpCAM+ cells, resulting in elevated TP53 expression and increased apoptosis. To our knowledge, this is the first report of cancer cell-derived exosomes that can inhibit the immune system by promoting immune cell apoptosis.